Physicochemical And Preliminary Study on Gc-MS Analysis of Prosopis Africana Seed (African Mesquite) Oil - Agubosi, O.C.P; Oluwafemi, R.A; Alagbe, J.O (Zien Journals, 2021)
A preliminary study was carried out to examine the various bioactive compounds and physicochemical properties of Prosopis africana seed oil (African mesquite). The extracted oil was yellow in colour with a yield of 10.73 % at liquid state, acid value, saponification, iodine, peroxide values ranged between 15.18 (mg NaOH/g of oil), 112.7 (mg/KOH/g of oil), 150.4 (gI2/100g of oil) and 27.75 (meq/kg) respectively. A total number of 24 bioactive compounds was identified using GC-MS this includes: 2-phenyl propane (3.09 %), 1,3,5-trimethyl benzene (4.80 %), prosogerin A (12.67 %), prosogerin B (10.06 %), prosogerin C (7.11 %), prosogerin D (4.05 %), prosogerin E (2.89 %), luteolin 7-O-β-D-glucoside (0.67 %), quercetin 3-O-rutinoside (4.88 %), isoprosopilosine (4.28 %), tryptamine (1.66 %), β-phenethylamine (5.63 %), gallic acid (0.57 %), 4-hydroxy benzoic acid (1.41 %), 2,4-bis (1-phenylethyl) phenol (9.60 %), 2,4,6- tris(1-phenylethyl) phenol (7.83 %), rhodoxanthin (1.67 %), ferulic acid (1.20 %), pheophytin A (1.54 %), pheophytin B (3.31 %), campsterol (2.80 %) and β-sitosterol (1.51 %). Prosogerins are the most abundant compounds in the sample and are known to posses antimicrobial, anti-inflammatory and capable of scavenging free radicals thus preventing diseases in animals. It was concluded that Prosopis africana seed oil can be used as potential alternative to antibiotics and can be used to bridge the gap between food safety and livestock production
Keywords: Prosopis africana; seed; oil; phytochemicals